Implementation of Setting Policy Parking in Manado City - Worang, Jeffry; Dilapanga, Abdul Rahman; Kairupan, Sisca Beatrix (JR Education, 2024)
This study aims to determine, analyze, and describe parking arrangements in Manado City and determinant factors in parking arrangements in Manado City. The type of research used in this study is descriptive qualitative, with a phenomenological approach. This study examines objects in natural conditions, where researchers act as the main instrument. Data collection techniques are carried out using the triangulation method (combined), and the research instrument used is interviews. Data analysis is inductive/qualitative, and the results of qualitative research emphasize meaning rather than generalization. The results indicate that overall, the study shows that parking arrangements in Manado City have brought some progress, but some issues still need to be fixed. Implementation of strategic steps that include data collection, zoning arrangements, strict supervision, use of technology, and increased socialization and community participation are the keys to achieving optimal parking arrangements and meeting community needs.